2023
DOI: 10.1088/1402-4896/acbdcf
|View full text |Cite
|
Sign up to set email alerts
|

New role of null lagrangians in derivation of equations of motion for dynamical systems

Abstract: The space of null Lagrangians is the least investigated territory in dynamics as these Lagrangians are identically sent to zero by their Euler-Lagrange operator, and thereby they are having no effects on equations of motion. A procedure that significantly generalizes the previous work, which appeared in Physica Scripta 97, 125213 (2022), is developed and used to construct null Lagrangians and then the corresponding non-standard Lagrangians, which represent a range of interesting dynamical systems. By u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…However, there is another family of Lagrangians called null Lagrangians (NLs), which make the E-L equation identically zero and are given as the total derivative of a scalar function [7]; the latter is called here a gauge function. The NLs were extensively studied in mathematics (e.g., [7,[39][40][41][42][43]) and recently in physics [44][45][46][47], but to the best of our knowledge, NSLs have not yet been introduced to biology and specifically, to its population dynamics. Therefore, in the following, we present the first applications of NLs to biology and its population dynamics.…”
Section: Null Lagrangians For the Population Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is another family of Lagrangians called null Lagrangians (NLs), which make the E-L equation identically zero and are given as the total derivative of a scalar function [7]; the latter is called here a gauge function. The NLs were extensively studied in mathematics (e.g., [7,[39][40][41][42][43]) and recently in physics [44][45][46][47], but to the best of our knowledge, NSLs have not yet been introduced to biology and specifically, to its population dynamics. Therefore, in the following, we present the first applications of NLs to biology and its population dynamics.…”
Section: Null Lagrangians For the Population Modelsmentioning
confidence: 99%
“…Recent studies of null Lagrangians demonstrated that there is a different condition that is obeyed by NLs and that this condition plays the same role for NLs as the E-L equation plays for standard and non-standard Lagrangians [46,47]. The condition can be written as…”
Section: Null Lagrangians For the Population Modelsmentioning
confidence: 99%
See 3 more Smart Citations